SCHOOL'S WORK QUALITY VS EDUCATIONAL PROCESS' DOCUMENTATION - MASTALERZ, Elżbieta (Trends in education, 2009)
Quality increase is one of modern phenomena. It is a primary goal, which today's educational systems should strive to achieve. One of many changes implemented by quality management is evaluation, which is a process of grading or describing events, purposeful and systematic, according to set standards. It's a process of gathering information about undertaken enterprises, that is subject to methodological rules. For education, quality equals accordance to standards. Those standards are set in fields of: requirements, achievement levels, behavior, progress indicators and proofs of achievements. School's work quality is measured by comparing its' effects with set goals and targets, diagnosis of certain schoolwork areas, regular measuring of school's work quality, investigating student's academic achievements. Measuring it means following school's educational activity and academic achievements, and comparing them with set quality standards. It is meaningful if it helps to enter higher quality levels. This article describes the documents and processes required for direct, systematic educational process, indispensable to proper monitoring of schoolwork quality.
Keywords: quality; documentation; evaluation.